HUBUNGAN STATUS FISIK ASA DENGAN WAKTU PULIH SADAR PADA PASIEN PASCA ANESTESI UMUM DI RS PKU MUHAMMADIYAH YOGYAKARTA - Azizah, Aisyah Nur; Yomanovanka, Kalistus Angger (Coping: Community of Publishing in Nursing, 2022)
Surgery is an invasive method of treatment that is carried out by making incisions in parts of human body. Patients undergoing surgery are given general anesthesia which is an act of eliminating pain centrally with loss of consciousness and there are effects or components of hypnotics, analgesics, muscle relaxation known as the triad of anesthesia. Patients under general anesthesia will recover and regain consciousness. There are several factors that can affect the length of time patient recovers, one of which is ASA physical status. ASA physical status is the physical status of pre general anesthesia patients which is divided into 6 classifications according to American Society of Anesthesiologists. This study aims to determine the relationship between ASA physical status and recovery time in patients after general anesthesia. This research applied quantitative research with cross sectional. The sampling technique used was purposive sampling, obtained 35 respondents who met the inclusion and exclusion criteria. Data analysis using Spearman correlation test. Results of this research showed that the difference in the average recovery time in patients with pre general anesthesia physical status criteria ASA I (13 minutes), ASA II (24 minutes), ASA III (34 minutes 44 seconds). The results of the Spearman correlation test to determine the relationship between ASA physical status and time to recover consciously obtained the results of 0,000 (p < 0,05), meaning that there is significant correlation between ASA physical status and recovery time in patients after general anesthesia.